Genetic diversity of the potentially therapeutic tapeworm Hymenolepis diminuta (Cestoda: Cyclophyllidea). (August 2019) - Řežábková, Lucie; Brabec, Jan; Jirků, Milan; Dellerba, Marc; Kuchta, Roman; Modrý, David; Parker, William; Jirků Pomajbíková, Kateřina
Abstract: The cestode Hymenolepis diminuta is highly prevalent in wild rat populations and has also been observed rarely in humans, generally causing no apparent harm. The organism has been studied for decades in the laboratory, and its colonization of laboratory rats has recently been shown as protective against some inflammation-associated disorders. Recently, H. diminuta has become a leading candidate for helminth therapy, an emerging method of "biota enrichment" used to treat or prevent inflammatory diseases of humans in Western society. While most of the experimental isolates of H. diminuta are identified based on typical morphological features, hymenolepidid tapeworms may represent complexes of cryptic species as detected by molecular sequence data. In the present study, we explored the diversity of laboratory-kept strains using partial sequences of two genes (lsrDNA and cox 1) and determined that H. diminuta isolates currently considered for therapeutic purposes in the US and Europe belong to a single, genetically nearly uniform lineage, showing only little genetic deviation from wild-caught isolates. Graphical abstract: Unlabelled Image Highlights: Hymenolepis diminuta stands as the only cestode being considered for therapeutic use. H. diminuta is maintained in cultures under laboratory conditions worldwide. Laboratory isolates of H. diminuta do not genetically differ from isolates from wild rats. Scientists deal with genetically uniform population of H. diminuta under laboratory conditions.